Trends in FDI movement of New Zealand economy over the last two decades: an analysis / Ershad Ali and Ronica Joyce Adriano - Ali, Ershad; Adriano, Ronica Joyce (Universiti Teknologi MARA Selangor, 2019)
Foreign Direct Investment has been the main source of capital for New Zealand economy during the last two decades. This paper analyses how FDI had changed the New Zealand economy over the years as a response to worldwide globalization. The study focuses on the background of the country’s inflow and outflow of FDI, its implications to the current period and the reasons why the country had experience certain challenges. It also covers how the economy was able to overcome the challenges. The study found that New Zealand, being a small economy compared to the world, has overcome the globalized economic challenges by its efficient management and appropriate policy. Findings of the study might be of interest for researchers, policy makers and economists.